2016
DOI: 10.5830/cvja-2016-007
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings in a cross-sectional study of human immunodeficiency virus (HIV) patients in Enugu, south-east Nigeria

Abstract: SummaryBackgroundElectrocardiographic (ECG) abnormalities are prevalent in subjects with human immunodeficiency virus (HIV) infection. In this study, three groups of subjects were investigated and the prevalence of ECG abnormalities was analysed.MethodsA cross-sectional study was carried out on adults between November 2010 and November 2011 at the University of Nigeria Teaching Hospital, Enugu, Nigeria. One hundred HIV-infected patients on highly active anti-retroviral therapy (HAART), 100 HIV-infected HAART-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
(29 reference statements)
4
27
1
Order By: Relevance
“…The higher prevalence of QTc prolongation observed among HIV patients compared to healthy controls in our study has been variously reported by other researchers ( 12 , 22 25 ). Various reasons that account for this include autonomic dysfunction ( 25 ) and other established predisposing factors to QTc prolongation such as female sex, drugs and electrolyte abnormalities ( 26 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher prevalence of QTc prolongation observed among HIV patients compared to healthy controls in our study has been variously reported by other researchers ( 12 , 22 25 ). Various reasons that account for this include autonomic dysfunction ( 25 ) and other established predisposing factors to QTc prolongation such as female sex, drugs and electrolyte abnormalities ( 26 ).…”
Section: Discussionsupporting
confidence: 86%
“…This is because the introduction of the Highly Active Anti-Retroviral Therapy (HAART) has significantly improved the survival of HIV patients and enabled them to live long enough to develop other systemic complications of the disease ( 3 ). Cardiovascular involvement in HIV/AIDS was recognized in the early days of the pandemic ( 4 ) and a wide spectrum of cardiovascular abnormalities ( 5 9 ) including electrocardiographic abnormalities such as corrected QT interval (QTc) prolongation ( 10 12 ) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible explanations can be treatment with lopinavir (LPV) and zidovudine (ZVD) in seropositive patients. 31 Shavadia et al. noticed similar findings.…”
Section: Resultsmentioning
confidence: 69%
“…Numerous studies have reported an increased prevalence of QT prolongation among HIV‐infected individuals compared to uninfected controls possibly due to concurrent administration of QT‐prolonging medications as well as the effect of the virus itself on the QTc interval 9‐12 . Table 1 summarizes six studies which compared the prevalence of QTc prolongation between HIV‐infected individuals vs. an uninfected control group 9,10,13‐16 . QT prolongation is a precursor for life‐threatening arrhythmias including torsades de pointes.…”
Section: Qt Prolongation/risk Of Torsades De Pointesmentioning
confidence: 99%